Predictors of Serological Cure in Syphilis Patients: A Retrospective Study at a Tertiary Hospital in Bandung, Indonesia - Achdiat PA; Rowawi R; Pujiastuti NR; Amalia F; Suwarsa O; Anandita R; Maharani RH (Infection and Drug Resistance)
Pati Aji Achdiat, Rasmia Rowawi, Nindayu Rizki Pujiastuti, Fatimah Amalia, Oki Suwarsa, Rafithia Anandita, Retno Hesty Maharani Department of Dermatology and Venereology, Faculty of Medicine Universitas Padjadjaran - Dr. Hasan Sadikin Hospital, Bandung, West Java, IndonesiaCorrespondence: Pati Aji Achdiat, Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin Hospital, Jl. Pasteur 38, Bandung, West Java, 40161, Indonesia, Tel +6281225955478 ext. 3449, Fax +62222032426, Email pati.aji.achdiat@unpad.ac.id Retno Hesty Maharani, Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin Hospital, Jl. Pasteur 38, Bandung, West Java, 40161, Indonesia, Tel +6281225955478 ext. 3449, Fax +62222032426, Email retno.hesty@unpad.ac.idIntroduction: Syphilis is an infection caused by the spirochete Treponema pallidum and transmitted through sexual intercourse. Regular monitoring is necessary to ensure affected patients have successfully attained a serological cure following medication. Despite receiving suitable medication, specific individuals in clinical settings do not succeed in achieving serological cure.Purpose: This study aims to determine the factors associated with the serological cure of syphilis at Dr Hasan Sadikin General Hospital Bandung, Indonesia.Material and Methods: The study procedures were carried out using a retrospective descriptive method. Secondary data were obtained from medical records at the Dermatology and Venereology Outpatient Clinic of Hasan Sadikin Hospital, Bandung, Indonesia, from 1 January 2018 to 31 December 2022.Results: The sample population comprised 266 cases of syphilis, consisting of 185 male and 81 female patients. The bivariate analysis results showed that patients aged less than 35 years had a serological cure rate of 75.4%, with a 3.89 times higher chance of achieving serological cure compared to those ≥ 35 years (p < 0.0001, OR = 3.89, 95% CI 1.85– 8.13). In addition, the proportion of serological cure was higher in patients with Venereal disease research laboratory test (VDRL) titers of ≤ 1:8 before therapy (OR = 0.61, 95% CI 0.28– 1.35, P = 0.226). Similar results were also obtained in those with HIV-negative (OR = 0.83, 9% CI 0.38– 1.81, P=0.648), and benzathine penicillin G therapy (OR = Reff, P = 0.226).Conclusion: An age of < 35 years was a highly influential factor in the success of syphilis therapy. This indicates that intervention and monitoring strategies should focus on this age group, especially in resource-limited settings. The most common time for serological cure in early syphilis was the 9th and 12th months, while the 3rd and 12th months were common in late syphilis.Keywords: serological cure, serofast, syphilis